Development of Learner Worksheets Based on PjBL Model to Increase Creativity on Material Changes in the Form of Objects - Sovi Ambarwati; Dwi Yulianti; Ryzal Perdana; Sugeng Sutiarso; Muhammad Nurwahidin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Creativity is the ability of individuals to express themselves so that they will produce new ideas and works. Creativity can be enhanced by creating innovative learning activities that encourage students to express themselves and provide creative ideas so that students' creativity continues to increase. This study aims to determine the development of PjBL-based SW, its attractiveness, and increased student creativity. Method: This research (R&D) uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Results: The results of this study indicate that 1) the product developed with the ADDIE model is declared